PENGEMBANGAN PERANGKAT PERKULIAHAN FISIKA DASAR MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN MIND MAP - Ilwandri Ilwandri (STKIP Rokania Pasir Pangaraian, 2020)
This research is motivated by the unavailability of Basic Physics lecture devices that are in accordance with the characteristics, conditions, abilities of students and curriculum demands. This can be seen from the results of curriculum analysis, student analysis and material analysis conducted. This study aims to develop Basic Physics Lecture devices using STAD type cooperative learning models aided by Mind Maps on valid Basic Physics Courses (in terms of content, presentation, and language), practical (in terms of ease of use and suitability with time), and effective (seen from the activities and student learning outcomes). This type of research is development research. The development model used is the 4D model which consists of 4 stages, namely: defining, designing, developing and disseminating. This research was conducted with 30 students. This development process results in a product in the form of lecture devices of the STAD type cooperative learning model assisted by the Mind Map on a valid, practical and effective Basic Physics Course. The results showed that the lecture tools produced were valid, practical, and effective. This is seen based on the value of the validity, practicality and effectiveness of lecturing devices. The value of the validity of the set of lectures by experts is 0.89 valid categories and by practitioners is 0.91 valid categories. Practicality value is obtained from the Lecturer response questionnaire and Student response questionnaire. The practicality value by lecturers is 87.2% categorized as very practical. The practicality value by students is 89.2% categorized as very practical. The effectiveness value of the lecture set is obtained from the assessment of student activity and learning outcomes. The value of student attitudes is 75.82% categorized as very good, the average value of student knowledge is 80.00% categorized as good, and the average value of student skills is 76.73% categorized as good. Thus, this research has produced physics lectures using STAD type cooperative learning models assisted with Mind maps on valid, practical, and effective Basic Physics Courses.